2023
DOI: 10.3390/ijms241914582
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Neuroinflammation in the Onset and Progression of Parkinson’s Disease

Anamaria Jurcau,
Felicia Liana Andronie-Cioara,
Delia Carmen Nistor-Cseppento
et al.

Abstract: Parkinson’s disease is a neurodegenerative disease exhibiting the fastest growth in incidence in recent years. As with most neurodegenerative diseases, the pathophysiology is incompletely elucidated, but compelling evidence implicates inflammation, both in the central nervous system and in the periphery, in the initiation and progression of the disease, although it is not yet clear what triggers this inflammatory response and where it begins. Gut dysbiosis seems to be a likely candidate for the initiation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 346 publications
0
7
0
Order By: Relevance
“…Various pathways have been reported as mechanisms by which intestinal microbiota and TLR2 signaling affect α-synuclein accumulation in PD [ 44 ]. Studies have shown that microglial activation in PD pathology can induce the accumulation of α-synuclein aggregates and the degeneration of dopaminergic neurons in the substantia nigra [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various pathways have been reported as mechanisms by which intestinal microbiota and TLR2 signaling affect α-synuclein accumulation in PD [ 44 ]. Studies have shown that microglial activation in PD pathology can induce the accumulation of α-synuclein aggregates and the degeneration of dopaminergic neurons in the substantia nigra [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, certain microbiota-derived antigens and metabolites can promote a “leaky gut” syndrome and elicit intestinal inflammation. It is currently acknowledged that peripheral inflammation is a potential risk factor in various neurodegenerative diseases, especially PD (for a review, see [ 10 , 32 , 33 , 34 ]). Reactive microgliosis within the SN, an increased number of major histocompatibility complex (MHC) II-positive cells in various brain areas and high levels of pro-inflammatory molecules are hallmarks of PD [ 10 ].…”
Section: Gut–brain Axis Correlates Microbiota With Neuroinflammationmentioning
confidence: 99%
“…It is currently acknowledged that peripheral inflammation is a potential risk factor in various neurodegenerative diseases, especially PD (for a review, see [ 10 , 32 , 33 , 34 ]). Reactive microgliosis within the SN, an increased number of major histocompatibility complex (MHC) II-positive cells in various brain areas and high levels of pro-inflammatory molecules are hallmarks of PD [ 10 ]. Furthermore, sustained activation of the immune system, manifested by increased levels of cytokines and chemokines, is evident in the blood and gut of PD patients [ 10 ].…”
Section: Gut–brain Axis Correlates Microbiota With Neuroinflammationmentioning
confidence: 99%
See 2 more Smart Citations